2011
DOI: 10.1016/j.regpep.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute and repeated restraint differentially activate orexigenic pathways in the rat hypothalamus

Abstract: Stress and obesity are highly prevalent conditions, and the mechanisms through which stress affects food intake are complex. In the present study, stress-induced activation in neuropeptide systems controlling ingestive behavior was determined. Adult male rats were exposed to acute (30 min/d × 1 d) or repeated (30 min/d × 14 d) restraint stress, followed by transcardial perfusion 2h after the termination of the stress exposure. Brain tissues were harvested, and 30 µm sections through the hypothalamus were immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 37 publications
2
24
0
Order By: Relevance
“…Although GC administration stimulates both orexigenic neuropeptides (see earlier), but during stressful events their expressions are differentially regulated (Kas et al, 2005). More precisely, acute and repeated restraint reduces the number of AgRP-expressing cells (Chagra et al, 2011), and brief session of inescapable foot shocks down-regulates AgRP mRNA levels in ARC in the rat hypothalamus (Kas et al, 2005). AgRP is known to be the natural antagonist for the type 4 melanocortin (MC-4) receptors mediating anorexigenic signals of melanocortins (Leibowitz and Wortley, 2004).…”
Section: Central Anorexigenic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…Although GC administration stimulates both orexigenic neuropeptides (see earlier), but during stressful events their expressions are differentially regulated (Kas et al, 2005). More precisely, acute and repeated restraint reduces the number of AgRP-expressing cells (Chagra et al, 2011), and brief session of inescapable foot shocks down-regulates AgRP mRNA levels in ARC in the rat hypothalamus (Kas et al, 2005). AgRP is known to be the natural antagonist for the type 4 melanocortin (MC-4) receptors mediating anorexigenic signals of melanocortins (Leibowitz and Wortley, 2004).…”
Section: Central Anorexigenic Effectmentioning
confidence: 99%
“…Food intake Anorexia (Bazhan et al, 2007;De Souza et al, 2000;Fryer et al, 1997;Harris et al, 2001;Krahn et al, 1990;Rybkin et al, 1997) Hyperphagia (Dallman, 2010;Dallman et al, 2005;Foster et al, 2009;la Fleur et al, 2005;Pecoraro et al, 2004) Mechanisms Stress induces anorexia due to decreased signaling of: AgRP (Chagra et al, 2011;Kas et al, 2005) NPY (Tempel and Leibowitz, 1994;White, 1993) due to increased signaling of: insulin? (Chavez et al, 1997;Warne, 2009) leptin?…”
Section: Q4mentioning
confidence: 99%
“…Restraint stress is regarded as a form of mild stress, as indicated by physiologic and neuroendocrine responses, however, it has been shown to increase expression of orexigenic peptides in the hypothalamus nonetheless (Chagra et al, 2011). Interestingly, the expression of orexigenic peptides seems to increase when restraint stress is repeated over time (Chagra et al, 2011) and it has been shown that feeding responses to restraint stress are maintained in the absence of the stressor (Tamashiro et al, 2007a). Mild restraint stress has the ability to increase the number of AgRP-expressing neurons, while simultaneously reducing α-MSH receptors, in the ARC (Chagra et al, 2011).…”
Section: Stress Modelsmentioning
confidence: 99%
“…Following a meal, CCK NTS neurons become activated and relay visceral input from the vagus to brain regions known to mediate changes in feeding (Rinaman, 2010). Interestingly, the same brain regions that are important for feeding behavior have also been shown to influence behavioral responses to emotionally relevant stimuli associated with fear, stress, and pain (Bernard and Besson, 1990; Bester et al, 2000; Casada and Dafny, 1992; Chagra et al, 2011; Han et al, 2015; LeDoux, 2000). Two such regions receiving especially dense innervation from CCK NTS neurons are the PBN and PVH.…”
Section: Introductionmentioning
confidence: 99%